Addressing Mental Health Access in Underserved West Africa: A Strategic Framework - (:unkn) unknown (My University, 2024)
Aim: To address mental health crisis focusing on the applicable framework for strengthening access in underserved West African communities. Problem Statement: The World Health Organizarion (WHO) states that approximately 450 million people have a mental disorder and about one-quarter of the population will be affected from mental ailment at some stages in their lifetime. Handling of crisis relating to mental health is underserved in some West African communities. Significance of Study: The high rise in the number of mental health cases in some underserved communities in West Africa has called for designing a workable and applicable framework to ameliorate this situation. Methodology: Previous literatures, journals, books, research write-ups and other related materials on the internet regarding to address mental health crisis focusing on the applicable framework for strengthening access in underserved West African communities were consulted. Discussion: Strengthening health systems in some underserved communities in West Africa to advance mental health care delivery adopting the WHO framework and other beneficial indigenous methods is achievable. These merged methodologies can increase the quality and nature of mental health care delivery systems. They can also increase the existing mental health care services in order to make them to be more effective and efficient in meeting the requirements of the people. With a strengthened health system, the condition of mental health delivery across West Africa will be improved. There is an emergency quest for rigorous effort between the policy makers, government and international organizations to execute the recommendations stated herein for an accessible, better and affordable mental health services for the mental well-being of the public in advancing mental health services and care. Conclusion: In conclusion, it is imperative to adopt and apply the elements of the framework stated in strengthening mental health
Keywords: African Research